Korelasi dukungan keluarga dan penyembuhan luka pasien diabetes mellitus di klinik perawatan luka - Mayang Indah Arinimi; Hermansyah Hermansyah; Wirda Hayati; Nuswatul Khaira (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Diabetes Mellitus (DM) disease requires long-term treatment so some patients experience difficulty in compliance with the nursing care plan. Family support for family members who experience DM is also still very low (45,8%) in providing care. Complications in DM patients can worsen the patient's health condition and even experience amputation due to circulation problems making it difficult for wounds to heal. Objectives: To analyze the correlation between family support and wound healing in DM patients.Methods: The quantitative research approach was designed with a cross-sectional study. The sample used was non-probability sampling with an accidental technique of 34 DM patients at the Istiqamah Wound Care Clinic, Aceh Besar Regency. Family support data was collected using interviews, while wound healing data used observation. The collected data in September 2023 were analyzed using the pearson correlation coefficient test with α=0,05.Results: Almost 70,0% of patients received high emotional support from the family and 50,0% of the DM wound healing was in the wound regeneration category. The correlation coefficient test (r) revealed that emotional support (r=0,669), instrumental support (r=0,874), informational support (r=0,480), and assessment support (r=0,377). Family support has a significant positive correlation with wound healing in DM patients (p<0,05). The higher the support provided by the family during treatment, the faster the wound healing process in DM patients.Conclusion: Family support, especially instrumental support, is needed in healing wounds in DM patients, so that the health of DM patients can be achieved optimally.